1994
DOI: 10.1210/mend.8.7.7984154
|View full text |Cite
|
Sign up to set email alerts
|

Pax-QNR/Pax-6, a paired box- and homeobox-containing gene expressed in neurons, is also expressed in pancreatic endocrine cells.

Abstract: After differential screening of a cDNA library constructed from quail neuroretina cells infected with the v-myc containing avian retrovirus MC29, we have isolated a cDNA clone Pax-QNR, homologous to the murine Pax6 which is mutated in the autosomal dominant mutation small eye (Sey) of the mouse and aniridia in man. Here we report the characterization of Pax-QNR/Pax-6 expression in the chicken, quail, and mouse pancreas. In situ hybridization performed with E3 chick embryos demonstrated that, in addition to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 0 publications
4
50
0
Order By: Relevance
“…The large overlap between neurons and pancreatic endocrine cells in the molecular program of differentiation (Ahlgren et al, 1997;Alpert et al, 1988;Gradwohl et al, 2000;Naya et al, 1997; Sosa-Pineda et al, 1997; Sussel et al, 1998;Turque et al, 1994) and the knowledge that nestin is a marker of neuronal stem cells (Cattaneo and McKay, 1990;Johansson et al, 1999;Lendahl et al, 1990) drove the search in the pancreas for a nestin-positive population that would generate the cells of the endocrine and exocrine lineages. Previous reports indicated that nestin was expressed by mesenchymal cells of pancreas during development (Selander and Edlund, 2002), by the epithelium of the pancreatic primordium, and by acinar but not endocrine cells produced by this embryonic layer (Delacour et al, 2004;Esni et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large overlap between neurons and pancreatic endocrine cells in the molecular program of differentiation (Ahlgren et al, 1997;Alpert et al, 1988;Gradwohl et al, 2000;Naya et al, 1997; Sosa-Pineda et al, 1997; Sussel et al, 1998;Turque et al, 1994) and the knowledge that nestin is a marker of neuronal stem cells (Cattaneo and McKay, 1990;Johansson et al, 1999;Lendahl et al, 1990) drove the search in the pancreas for a nestin-positive population that would generate the cells of the endocrine and exocrine lineages. Previous reports indicated that nestin was expressed by mesenchymal cells of pancreas during development (Selander and Edlund, 2002), by the epithelium of the pancreatic primordium, and by acinar but not endocrine cells produced by this embryonic layer (Delacour et al, 2004;Esni et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that islet cells and neurons have similar molecular phenotypes (Ahlgren et al, 1997;Alpert et al, 1988;Gradwohl et al, 2000;Naya et al, 1997;Sander et al, 2000;Sosa-Pineda et al, 1997;Sussel et al, 1998;Turque et al, 1994) raised the possibility that precursor cells of islets, like those of brain, express the intermediate filament nestin (Cattaneo and McKay, 1990;Lendahl et al, 1990), a classical marker of neuronal stem cells. This possibility was supported by the discovery of nestin ϩ cells in epithelial cells of the pancreatic bud of mouse embryos from e-10 to e-15 (Esni et al, 2004), raising the prospect that these cells were endocrine precursor cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Pa 6, Pa 4 is expressed in beta cells [13]. Although Pa 6 is expressed in all four types of islet cells and in other organs including eyes and the central nervous system [6,7], Pa 4 is specifically expressed in beta cells [13]. The Pa 6 protein binds to a common element in the glucagon, insulin, and somatostatin promoters, and transactivates the glucagon and insulin promoters [8].…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In particular, PAX4 and PAX6 are essential for development of pancreatic islet cells as well as endocrine cell development in the small intestine and stomach. [14][15][16] Although PAX8 has been most studied in renal tissues and neoplasms, 17 it has been recently recognized as a useful marker in distinguishing ovarian from breast carcinoma, 18 and as a marker of thyroid epithelial neoplasms. 19 Moreover, our group recently observed intense PAX8 reactivity in pancreatic neuroendocrine tumors and normal pancreatic islets in a large tissue microarray evaluation of PAX8 immunoreactivity of non-renal tissues/neoplasms.…”
mentioning
confidence: 99%